ナンキョク ニオケル ライダー カンソク ノ ケイカク f. キョクイキ デンリソウ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 2 - 藤原, 玄夫; フジワラ, モトヲ; 北村, 泰一; キタムラ, タイイチ; FUJIWARA, Motowo; KITAMURA, Tai-ichi (1980)
P(論文) ライダーによる南極の中層大気圏の探査を提案する.これはYAGレーザーおよびYAGレーザー励起色素レーザーをライダー送信系に用いて,成層圏のエアロゾル,オゾンや中間圏,下部熱圏のアルカリ金属原子,エアロゾル等の微量成分と,大気分子個数密度の高度分布およびその時間的変動を精密に測定しようとするものである.南極のライダー観測は,中層大気圏の組成的,力学的構造のグローバルな理解のためにきわめて重要であり,また,オーロラなどの極域電離圏における電磁気的じょう乱に対する中層大気の応答を調べる上できわめて有意義である. Lidar observations of the middle atmosphere in the Antarctic are proposed. Vertical profiles and their time variabilities of air molecules and minor constituents of the atmosphere, such as aerosols and ozone in the stratosphere and alkali metal atoms and aerosols in the mesosphere and the lower thermosphere, will be measured accurately by using a lidar system, the transmitter of which consists of a YAG laser and a dye laser pumped by the YAG laser. The lidar observations in the Antarctic are very significant in knowing the global structure of atmospheric constituents and dynamics in the middle atmosphere. Moreover, they will provide important information about the response of the middle atmosphere to the electromagnetic disturbance such as aurora in the polar region ionosphere. departmental bulletin paper